OPTIMALISASI EFEKTIVITAS MANAJEMEN KANTOR MELALUI BUDAYA KERJA DAN GAYA KEPEMIMPINAN - Ardellia, Azahra Sazida; Sukmawati , Sheima (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to optimize the effectiveness of office management by examining the role of work culture and leadership style in the branch offices of Bank Syariah Indonesia (BSI). The office plays a crucial role in various economic sectors, not only as a place for management and administrative tasks but also as a vital service center in communication and decision-making. The effectiveness of office management is measured by the office's ability to manage, plan, and control its activities to achieve predetermined goals. A good work culture plays an important role in improving employee productivity and performance. In addition, an appropriate leadership style also significantly contributes to employee motivation and performance. This research employs a qualitative method with interviews as the main data collection technique. The results show that the implementation of a positive work culture and effective leadership style can enhance the effectiveness of office management at BSI, ultimately contributing to improved service quality and the achievement of strategic goals.